Revitalization and Development of the Green Real Estate of Riga City (Baltic Journal of Real Estate Economics and Construction Management, 2013)
The general purpose of the scientific paper is to reflect the basic research results in the area of the management of the green real estate of Riga City. The interpretation of the term “green real estate” includes parks, gardens, squares, alleys and other green urban open space. Scientific research discussed within the framework of the paper has an observational case study design. The main results of the research are related to the study of the management process of the revitalization and development of parks and open spaces in the City of Riga. Based on the research results, conclusions and elaborations received within the study, recommendations for the improvement of the management of green space of Riga City are developed.